1990
DOI: 10.1002/eji.1830200426
|View full text |Cite
|
Sign up to set email alerts
|

T cell receptor gene rearrangements of T lymphocytes infiltrating the liver in chronic active hepatitis B and primary biliary cirrhosis (PBC): Oligoclonality of PBC‐derived T cell clones

Abstract: Immunological events are involved in the pathophysiology of chronic active hepatitis as indicated from the accumulation of T lymphocytes at the site of tissue damage. We generated T cell clones from liver biopsies of 3 patients with chronic active hepatitis B and 2 patients with primary biliary cirrhosis. These T cell clones (n = 84) were analyzed by means of T cell receptor (TcR) beta gene rearrangements to determine whether the infiltrate consists of a polyclonal or oligoclonal T cell population. The vast ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
2

Year Published

1991
1991
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 44 publications
1
47
2
Order By: Relevance
“…These observations led to the use of anti-TCR mAbs and vaccination with synthetic peptides of the CDR2 and CDR3 TCR regions; both proved beneficial in experimental allergic encephalomyelitis (33,35). Limited TCR gene rearrangements have been found in lymphocytes infiltrating brains of multiple sclerosis patients (36), synovial tissues of rheumatoid arthritis patients (37), liver of primary biliary cirrhosis (38), and in the thyroid ofthyroiditis patients (39). In multiple sclerosis plaques a dominant CDR3 sequence identical with that of TCR clones specific for myelin basic protein has been found (40).…”
Section: Discussionmentioning
confidence: 99%
“…These observations led to the use of anti-TCR mAbs and vaccination with synthetic peptides of the CDR2 and CDR3 TCR regions; both proved beneficial in experimental allergic encephalomyelitis (33,35). Limited TCR gene rearrangements have been found in lymphocytes infiltrating brains of multiple sclerosis patients (36), synovial tissues of rheumatoid arthritis patients (37), liver of primary biliary cirrhosis (38), and in the thyroid ofthyroiditis patients (39). In multiple sclerosis plaques a dominant CDR3 sequence identical with that of TCR clones specific for myelin basic protein has been found (40).…”
Section: Discussionmentioning
confidence: 99%
“…The study of TCR b gene rearrangements of cell clones obtained from PBC liver biopsies demonstrated different degrees of oligoclonality of the infiltrating T cells. 114,115 The use of TCR Vb or Jb genes by PDC-E2 [163][164][165][166][167][168][169][170][171][172][173][174][175][176] -reactive T-cell clones is also highly diverse with GXG or GXS motifs found within the complementaritydetermining region 3 (CDR3) of all T-cell clones. 116 When autoreactive T-cell frequencies are compared among different tissues of patients with PBC, PDC-E2 163-176 -reactive precursor T cells are 100-150-fold more represented in the hilar lymph nodes and the liver compared to the peripheral blood, possibly with changes in different disease stages.…”
Section: Immunopathogenesis Of Pbcmentioning
confidence: 99%
“…It mimics human viral and autoimmune hepatitis in many aspects (8)(9)(10). Con A-induced hepatitis is accompanied by an increase in the serum concentration of several cytokines, including TNF-α, IFN-γ, IL-6, and IL-1.…”
Section: Introductionmentioning
confidence: 99%